Право на доступ до інформації - Рудник, Людмила Іванівна (НУБіП України, 2015)
Дисертація на здобуття наукового ступеня кандидата юридичних наук за спеціальністю 12.00.07 – адміністративне право і процес; фінансове право; інформаційне право. – Національний університет біоресурсів і природокористування України, Київ, 2015. Роботу присвячено дослідженню права на доступ до інформації. Здійснено історіографічний аналіз досліджень права на доступ до інформації. Визначено методологічні засади права на доступ до інформації. Проаналізовано поняття та зміст права на доступ до інформації. Уточнено право на доступ до інформації як елемент правового статусу людини й громадянина. Схарактеризовано порядок доступу до інформації з обмеженим доступом. Прослідковано сучасні тенденції розвитку інформаційних відносин у сфері доступу до інформації. Здійснено аналіз міжнародного досвіду правового регулювання права на доступ до інформації та рекомендації щодо його імплементації в національне законодавство України. Обґрунтовано пропозиції та рекомендації щодо шляхів підвищення ефективності правового регулювання права на доступ до інформації в Україні.
Thesis for the scientific degree of Candidate of Legal Sciences on specialty 12.00.07 – administrative law and procedure, financial law, informational law. – National University of Life and Environment of Science of Ukraine, Kyiv, 2015. Thesis is dedicated to the right on access to information. Historic analyze of the researches of the right on access to information was carried out. Methodological basis of the right on access to information were defined. Notion and content of the right on access to information were analyzed. The right on access to information as an element of legal status of a person and a citizen was specified. The order of the access to information with limited access was characterized. Modern trends of development of information relations in the sphere of access to information were followed. Analyze of international experience of the legal regulation of the right on access to information was carried out and recommendations on its implementation into Ukrainian domestic legislation were offered. Proposals and recommendations on directions of improvement of the legal regulation of the right on access to information in Ukraine were grounded.
Keywords: інформаційне законодавство; інформаційне звернення; інформаційне право; інформаційний запит; інформаційні правовідносини; інформація; інформація з обмеженим доступом; категорія доступу; право на доступ до інформації; право на інформацію; режим доступу; свобода слова; information legislation; information appeal; information law; information reques; information legal relations